ОСОБЛИВОСТІ МІКРОСТАЦІАЛЬНОЇ ДИФЕРЕНЦІАЦІЇ СПЕКТРІВ ЕКОМОРФ УГРУПОВАНЬ АМФІБІОТИЧНИХ КОМАХ ГІДРОЕКОСИСТЕМ УКРАЇНСЬКИХ КАРПАТ - Hushtan, K. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2021)
The article is devoted to the spectra of ecomorphs of amphibiotic insect communities in hydroecosystems of the Ukrainian Carpathians.Nowadays, an investigation of ecomorphs is very urgent for ascertainment of human’s influence on the hydroecosystems. The human impact leads to a decrease in the number of certain ecomorphs and an increase in the number of others.The ecomorphic spectra of amphibiotic insects studied communities show a clear response to anthropogenic changes in the hydrological state of aquatic ecosystems. This affects the change in the quantitative ratio or the disappearance of characteristic sets of ecomorphs at the level of classes and subclasses. Transformations in the direction of formation of ecomorphic-monotypic groups, with dominance of only one subclass are noted.Due to the natural heterogeneity of the alluvial composition of the substrate, species richness of amphibiotic insects communities of is characterized by high ecomorphological diversity. Sets of ecomorphs, which are characteristic of a certain type of granulometric composition of flowing reservoirs, fall out in the anthropogenically changed stream.The foundations of comprehensive monitoring of hydroecological state of model streams has been laid down, based on analysis of ecomorph spectra of amphibionts according to its classifications. The microstation distribution of amphibiotic larvae insects is defined. The common set of ecomorph has been specified, depending on the typology of the substrate. The possibilities of use of amphibiotic ecomorph spectrum for bioindication of estimation of hydrological condition of watercourses of the Ukrainian Carpathians have been analyzed.